Stereotypes about aging, fears and perception about happiness: a sociodemographic analysis - López Fernández, Verónica (2020)
The present investigation was oriented to explore the links between negative stereotypes about aging, fears about old age, satisfaction with life and certain sociodemographic characteristics. For this purpose, a cross-sectional quantitative empirical study of descriptive-correlational scope was designed. A sample of 314 Spaniards was formed (74% women, Medad = 38 years), selected according to a sampling by availability. The participants answered a selection of instruments to measure the constructs under study. On the collected data, descriptive and correlational analyzes were carried out. The results show that there are no differences in any of the variables studied according to sex, but there are greater negative stereotypes among those who live with older adults. Age is negatively associated with both stereotypes and fears and satisfaction with life. Finally, negative stereotypes about aging are linked to lower levels of life satisfaction projected to five years. The findings are discussed and directions for future studies in the area are indicated.